Ali Alatas address at the National Press Club on 2 March 1989 - Alatas, Ali, 1932-2008.; National Press Club (Australia) (1989)
Mr Alatas spoke about Australian Indonesian relations, reopening of "Normsouten dialogue"; Pan Pacific economic agreement; the Australian media's poor representation of Indonesia; relations with Papua New Guinea; death of 6 Australian journalists in East Timor; Civil war; Indonesian Chinese relations.
Photographs available.
Also available online
Ali Alatas was the Indonesian Foreign Minister at the time of this recording.
Timed summary available.
Keywords: Indonesia -- Foreign relations; Australia -- Foreign relations -- Indonesia